Establishing Colonial Rule in a Frontier Encomienda: Chile’s Copiapó Valley under Francisco de Aguirre and His Kin, 1549–1580. - Garrido, Francisco; Figueroa, Erick (Latin American Research Review, 2024)
This article explores how Francisco de Aguirre used the Copiapó Valley encomienda to negotiate political power during the transition from conquest to colonial rule in northern Chile. Simultaneously, we analyze the circumstances of how a native society was incorporated into the Spanish Empire after a decade of fighting and resistance on the fringes of the empire. The strategic use of the fear of native rebellions to close the road from Peru to Chile gave Aguirre enough power to negotiate an important political position, which in the future would clash with the colonial authorities. Copiapó Valley’s peripheral location in the southernmost Atacama Desert constituted a political gray zone for the colonial administration. This space contributed to consolidating power for Aguirre and enabled locals some negotiation power within the possibilities afforded by the colonial system.